Pengenalan digital marketing dalam meningkatkan bisnis usaha mikro - Siyamto, Yudi; Wijayanti, Irine Diana Sari; Subiyantoro, Ary; Suliantoro, Suliantoro; Subandi, Subandi (Penamas: Journal of Community Service, 2024)
Problems in online marketing knowledge for women farming groups include a lack of understanding of effective digital marketing strategies and limited technological accessibility, which hinders optimizing digital marketing and increasing farmers' income and business opportunities. The solution to this problem is to provide online marketing knowledge and skills for farmers through a comprehensive training and mentoring program. This program includes understanding digital marketing strategies, the use of online platforms, engaging content, and consumer behavior. Training helps women farming groups face online marketing challenges. The material is presented in simple and accessible language, and collaborative workshops strengthen farmers' knowledge and skills.